Modelling And Control Of A Semi-Active Magnetorheological Damper For Engine Mounting Systems - Sariman, Mohamad Zaharudin (2016)
Multiple operating modes in advanced automotive powertrain technologies such as hybrid propulsion and cylinder deactivation require adaptable engine mounting systems. The use of magnetorheological (MR) fluid dampers for semi-active engine mounting systems offers the prospect of reducing the engine vibration by providing controllable damping forces. Controlling the semi-active engine mounting systems is challenging. The control should not only adequately provide the desired damping forces but also account for the vibration reduction. The aim of this study are to develop a force tracking control for a MR fluid damper model based on the characteristics obtained from the measurements and to assess the effectiveness of the vibration reduction control applied to the semi-active engine mounting system. The MR fluid damper unit was built in-house and was characterized using a damping force test rig. Based on the empirical data, the force tracking control was modelled based on the PI controller in Matlab Simulink software to provide desired damping forces. With sinusoidal forces generated by an electric motor, a scale model of three-degree-of-freedom (3-DOF) passive engine mounting system was built in-house to verify a mathematical model developed using the software. Then the 3-DOF model was added with the MR fluid damper model and the vibration attenuation control was applied to the semi-active engine mounting system using the Fuzzy-Tuned-PID controller. The results show the controller gives improvements in terms of Root mean square (RMS) and maximum peak variation as compared to the passive system.